Clinical Features of Adult Patients with Acute Hepatitis B Virus Infection Progressing to Chronic Infection - Kojiro Michitaka; Atsushi Hiraoka; Yoshio Tokumoto; Keiko Ninomiya; Tomoyuki Ninomiya; Norio Horiike; Masanori Abe; Yoichi Hiasa (International Journal of Hepatology)
Background. Information regarding the progression of acute hepatitis B virus (HBV) infection to chronic infection in adults is scarce. Methods. Twenty-five adult patients with acute HBV infection (14 men and 11 women, 18–84 years old), whose clinical features progressed to those of chronic infection (group A) or did not (group B), were studied retrospectively. Results. There were 3 and 22 patients in groups A and B, respectively. Two of the 3 patients of group A lacked the typical symptoms of acute hepatitis. No differences were found between groups with respect to age, sex, or HBV genotypes. However, total bilirubin and alanine aminotransaminase levels were significantly lower in group A. Conclusions. Three of the 25 adult patients with acute HBV infection progressed to chronic infection. Hepatitis was mild in these patients. Patients with mild acute hepatitis B or unapparent HBV infection may have a higher risk of progressing to chronic infection.